Musculoskeletal Disorders and Quality of Life of Sugarcane Farmers in the Northeast of Thailand: A Cross-sectional Analytical Study - Narupawan Prommawai; Wongsa Laohasiriwong; Kessarawan Nilvarangkul (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Musculoskeletal Disorders (MSDs) were directly associated with Quality of Life (QOL). It could cause various adverse consequences to daily life function, psychological health, work capacity and income. Aim: To identify the prevalence of MSDs and its association with QOL among sugarcane farmers. Materials and Methods: This cross-sectional analytical study was conducted among 529 samples selected through multistage random sampling from 3 provinces of the Northeast (NE) of Thailand to respond to the WHO-QOLBREF questionnaire. Multiple logistic regression was administered to determine the association between MSDs and QOL when other covariates were controlled. Results: It was found that as high as 74.29% (95% CI: 70.83- 77.84) of sugarcane farmers had MSDs and 36.29% (95% CI: 32.29-40.49) had poor QOL. MSDs were significantly associated with poor QOL (Adjusted OR=3.01; 95% CI: 1.84- 4.94; p<0.001). Other significant covariates were psychological factors including: depression (Adjusted OR=2.09; 95% CI:1.41- 3.10; p<0.001), high and severe levels of stress (Adjusted OR=2.11; 95% CI: 1.43-3.13; p<0.001), worked >8 hours per day (Adjusted OR=2.45; 95% CI: 1.57-3.81; p<0.001), and had monthly income ≤13,000 Baht (Adjusted OR=1.69; 95% CI:1.14- 2.52; p=0.008). Conclusion: MSDs and other covariates including psychological factors, depression, severe levels of stress, long working hours and low income were associated with poor QOL. Therefore, ergonomic behaviour modification including body preparation before work, proper working postures, and rehabilitation were needed to improve the QOL among the sugarcane workers in Northeast Thailand.